Management of High Cardiovascular Risk in Diabetic Patients: Focus on Low Density Lipoprotein Cholesterol and Appropriate Drug Use in General Practice - Rottura, Michelangelo; Scondotto, Giulia; Barbieri, Maria Antonietta; Sorbara, Emanuela Elisa; Nasso, Chiara; Marino, Sebastiano; Scoglio, Riccardo; Mandraffino, Giuseppe; Pallio, Giovanni; Irrera, Natasha; Imbalzano, Egidio; Squadrito, Giovanni; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aim of the study was to evaluate the management of high cardiovascular risk (CVr)in diabetic patients by exploring the prescribing behaviour in a setting of General Practitioners (GPs). A retrospective cohort study was carried out using the data recorded between 2018-2020 in the clinical database of 10 GPs. Diabetes was defined using International Classification of Diseases (ICD-9-CM) coding (250*) or using laboratory parameters (hyperglycemia condition: ≥126 mg/dl). Cohort was described stratifying by demographic, clinical and therapeutic characteristics and laboratory tests. Both CVr and statin prescriptions were evaluated; adherence to statin therapy (medication possession ratio, MPR ≥80) was calculated in accordance with low density lipoprotein cholesterol (LDL-C) target. Multivariate logistic regression models with adjusted Odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) were calculated to identify predictors of lipid modifying agents use and achieved target therapy; moreover, glucose-lowering drugs use was evaluated. Out of 13,206 people screened, 1,851 (14.0%) patients were affected by diabetes mellitus (DM), and 1,373 were identified at high/very high CVr. Of them, 1,158 (84.3%) had at least one measurement of LDL-C, and 808 (58.8%) received a prescription with at least one lipid-lowering drug (LLD). Patients at high/very high CVr treated or not treated with LLD, reached the LDL-C target in 24.0% and 10.3%, respectively (p<0.01). Furthermore, 34.6% of patients treated with high intensity lipid-lowering drugs and adherent to therapy showed LDL-C values below the therapeutic target. Out of 1,373 patients at high/very high CVr, 958 (69.8%) had at least one prescription of glucose-lowering drugs. Of them, 52.0% (n= 498) were prescribed not in agreement with the current guidelines. More specifically, 392 patients (40.9%) were treated with metformin only, while the remaining 106 (11.1%) were treated with metformin together with hypoglycaemic agents other than glucagon-like peptide-1 receptor agonists (GLP1-RA) or sodium-glucose-transporter 2 (SGLT2) inhibitors. Our results suggest the urgent need to improve the management of diabetic patients at high and very high CVr in the real life, in order to reduce the burden of diabetes on the health system.